Analysis of UD. GAJAH MAS and the Export Process - Bima Ramadhan B; Andre Wijaya; Olivia Kurniawan; Stephani Stephani (Journal of the Community Development in Asia (JCDA), 2018)
This paper discusses the analysis of UD. GAJAH MAS and the export process. UD GAJAH MAS itself is a company that produces cotton seed oil. The scarcity of this product is the company's advantage to be able to penetrate the international market. This paper aims to analyze the company's export process and analyze the scarcity of cotton seed oil products which are rarely produced by competing companies. The analytical method that we use is by directly interviewing the owner of the company. We use SWOT analysis to know the strengths and weaknesses of UD. GAJAH MAS. Thus market forces and the company's market weakness will be seen. Then combined with the international market potential to find out the export activities carried out by the UD company. ELEPHANT MAS. From the results of the research we conducted, it was underlined the scarcity of kapok seed oil products which are still experienced in other countries, such as Korea, America and even Europe. With the scarcity of cotton seed oil products have an impact on the high demand from abroad, which requires UD. GAJAH MAS conducts export activities abroad. The conclusion is that with the scarcity of companies that make cotton seed oil products have a positive impact on UD. GAJAH MAS sales, because with the high demand for foreign markets, the company has carried out the export process, and we also analyze the terms and conditions when exporting overseas. Then also learn about the estimated budgeted costs for exporting to various countries.